2020
DOI: 10.3390/rs12203363
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Agricultural Vulnerability to Drought in a Heterogeneous Environment: A Remote Sensing-Based Approach

Abstract: Agriculture is one of the fundamental economic activities in most countries; however, this sector suffers from various natural hazards including flood and drought. The determination of drought-prone areas is essential to select drought-tolerant crops in climate sensitive vulnerable areas. This study aims to enhance the detection of agricultural areas with vulnerability to drought conditions in a heterogeneous environment, taking Bangladesh as a case study. The normalized difference vegetation index (NDVI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…According to (Malik et al, 2019) the relationship between LST and NDVI has shown a strong negative correlation in summer, rainy, and winter seasons (R 2 > 0.9). The use of the NDVI threshold and the consideration of separating croplands from other land cover types reduces the inclusion of misclassified drought areas, thereby improving agricultural drought estimation (Faridatul & Ahmed, 2020). The combination of the NDVI and LST provides extremely useful information for agricultural drought monitoring and early warning systems for farmers with a high negative correlation (Sruthi & Aslam, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Malik et al, 2019) the relationship between LST and NDVI has shown a strong negative correlation in summer, rainy, and winter seasons (R 2 > 0.9). The use of the NDVI threshold and the consideration of separating croplands from other land cover types reduces the inclusion of misclassified drought areas, thereby improving agricultural drought estimation (Faridatul & Ahmed, 2020). The combination of the NDVI and LST provides extremely useful information for agricultural drought monitoring and early warning systems for farmers with a high negative correlation (Sruthi & Aslam, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, due to the sparse nature of infrastructure networks in major countries', continuous rainfall records are few or impossible to gather promptly. In addition, meteorological drought indices, e.g., SPI, RAI, and SPEI, have been commonly used and limited by the distribution of weather stations with the provision of only point data (Faridatul & Ahmed, 2020). Therefore, they failed to visualize the spatial detail with the inability to determine drought susceptibility across spatial units, thereby decreasing the reliability of the drought index.…”
Section: Resultsmentioning
confidence: 99%
“…Trong bối cảnh tác động của biến đổi khí hậu và tình trạng hạn hán tới các hoạt động kinh tế, xã hội có xu hướng gia tăng và ngày càng trở nên trầm trọng, công tác nghiên cứu, đánh giá và dự báo nhằm đưa ra các cảnh báo sớm và các biện pháp phòng chống hạn hán là việc làm cấp thiết, đem lại lợi ích trực tiếp đến đời sống xã hội. Việc ứng dụng các công cụ tiên tiến như mô hình hoá, vệ tinh viễn thám, hệ thống thông tin địa lý (Geographic Information System -GIS) có thể đem lại nhiều lợi ích và khắc phục những hạn chế về phạm vi không gian và thời gian của các biện pháp quan trắc truyền thống trong công tác đánh giá và dự báo hạn hán nói riêng và quản lý tài nguyên nước nói chung [3][4][5][6][7][8].…”
Section: Giới Thiệuunclassified
“…NDVI is a well-known vegetation index [54]. It is frequently used in studies aimed at analyzing the impact of drought on vegetation, the results being satisfactory [55,56]. The negative values of the NDVI anomaly (less than −1) represent browning vegetation, when they are between −1 and 1 they represent the vegetation in normal vegetation conditions, and when they are over 1 they represent greening vegetation.…”
Section: Sma Value Drought Categorymentioning
confidence: 99%